2006
DOI: 10.1186/1471-230x-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcome of bleeding pseudoaneurysm associated with chronic pancreatitis

Abstract: Background: A bleeding pseudoaneurysm in patients with chronic pancreatitis is a rare and potentially lethal complication. Optimal treatment of bleeding peripancreatic pseudoaneurysm remains controversial. This study reports on experience at Chang Gung Memorial Hospital (CGMH) in managing of bleeding pseudoaneurysms associated with chronic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 19 publications
(31 reference statements)
0
80
1
7
Order By: Relevance
“…Such major resections in a patient who is already haemodynamically unstable are fraught with mortality as high as 43% for pancreatic head resections and 16% for body and tail resections. 16 Surgical haemostasis and angioembolisation are always complimentary. In the background of a negative endovascular angiography, in a haemodynamically stable patient blind angioembolisation can be attempted based on CT angiography findings.…”
Section: Table 3 Results-endovascular Angioembolisationmentioning
confidence: 99%
“…Such major resections in a patient who is already haemodynamically unstable are fraught with mortality as high as 43% for pancreatic head resections and 16% for body and tail resections. 16 Surgical haemostasis and angioembolisation are always complimentary. In the background of a negative endovascular angiography, in a haemodynamically stable patient blind angioembolisation can be attempted based on CT angiography findings.…”
Section: Table 3 Results-endovascular Angioembolisationmentioning
confidence: 99%
“…(2,9,11,18) Gambiez et al (19) presented in his study that the majority of his patients were surgically treated and no signs of recurrent bleeding were present after definitive pancreatic surgery. He also concluded that angiographic methods might associate other severe complications such as necrosis of the duodenum or the development of spleen abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of pseudoaneurysm formation in pancreatitis include inflammation with enzymatic digestion of the pancreatic or peripancreatic artery, visceral artery erosion by pseudocysts, and pseudocyst erosion into the bowel wall and intramural artery. 9) Most pseudoaneurysms commonly present with abdominal pain or gastrointestinal hemorrhage or as a pulsatile abdominal mass accompanied by bruit. 3,8) As in this case, obstructive jaundice is an extremely rare clinical symptom of hepatic artery pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 99%